Domestic Tourist Experience Quality sebagai Kunci Sukses Pengembangan Wisata Halal di Sumatera Barat - Mariyanti, Eka; Putri, Siska Lusia; Sari, Puti Embun (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2024)
West Sumatra is included in the top 10 provinces that are prioritised in the development of halal tourism in Indonesia, West Sumatra proves that they are in the top 5 category of Indonesia's halal tourism provinces in the GMTI and IMTI surveys. The label as a halal tourist destination can certainly attract Muslim tourists to visit West Sumatra to welcome Visit Beautiful West Sumatra 2023. This study seeks to explain the influence of Halal Experience variables, tourist experience quality, on revisit intention and perceived value variables and tourist satisfaction as mediating variables. The sampling in this study used a non-probability sampling method with purposive sampling technique, namely the criteria for domestic tourists or archipelago tourists who have visited West Sumatra. This research is assisted by SEM-PLS statistical software which is used to evaluate the model and measurement structure, the research design is quantitative and descriptive. The population in this study were 226 tourists who had visited West Sumatra who were assisted by the G*power tool to get the number of respondents. Abstrak Sumatera barat termasuk dalam 10 besar provinsi yang diprioritaskan dalam pengembangan wisata halal di Indonesia, Sumatera Barat membuktikan bahwa mereka masuk kategori top 5 provinsi wisata halal Indonesia dalam survei GMTI dan IMTI. Label sebagai destinasi wisata halal tentunya dapat menarik wisatawan muslim untuk berkunjung ke Sumatera Barat untuk menyambut Visit Beautiful West Sumatra 2023. Penelitian ini berusaha menjelaskan pengaruh variabel Halal Experience, tourist experience quality, terhadap revisit intention serta variable perceived value dan tourist satisfaction sebagai variable mediasi. Adapun pengambilan sampel dalam penelitian ini menggunakan metode non probability sampling dengan teknik purposive sampling yaitu dengan Kriteria wisatawan domestik atau wisatawan nusantara yang pernah berkunjung ke Sumatera Barat. Penelitian ini dibantu oleh software statistik SEM-PLS yang digunakan untuk mengevaluasi model dan struktur pengukuran, desain penelitian adalah kuantitatif deskriptif. Populasi dalam penelitian ini adalah 226 wisatawan yang pernah berkunjung ke Sumatera Barat yang dibantu tools G*power untuk mendapatkan jumlah responden.